PENGARUH CEKAMAN KEKERINGAN TERHADAP RESPON FISIOLOGIS PERKECAMBAHAN BENIH KACANG TANAH (Arachis hypogaea L) - Renan Subantoro (MEDIAGRO, 2014)
The aim of this study are to determine the effect of various percentages of water provision at field capacity (drought) to the hypothetical vigor index and germination of peanut (Arachis hypogaea L) to be the one month seedlings age at regosol ground. The treatments were the percentage of moisture content on a variety of field capacity that 100%, 75%, 50% and 25%. The results of this study are: 1) the highest hypothetical vigor index value obtained in the water giving treatment of 100% on the condition of the field capacity (100% KL), followed by vigor subsequent value in the provision of water 75%, 50% and the lowest 25% of field capacity. 2) Water stress drought affects the parameter number of leaves, seedling height, leaf area, fresh weight and dry seeds, stem diameter and root length seeds groundnut to 4 weeks seedlings. Keywords: Germination, peanuts, physiology, water stress